Pathways of the past: the imprint of memory - Horn, Gabriel (Nature reviews. Neuroscience, 2004)
Key Points In imprinting, very young, visually naive chicks, when exposed to a moving visual stimulus, will approach the object and learn its characteristics. Subsequently, the chick will prefer the imprinted object over other objects. Imprinting offers a unique opportunity to study the neural representation of a learned visual object, and studies in recent years have provided much information about the neural correlates of imprinting. When chicks are exposed to an imprinting stimulus, RNA synthesis increases in part of the forebrain — the intermediate and medial hyperstriatum ventrale (IMHV). Destruction of this area impairs imprinting or eliminates an acquired preference. This and other evidence supports the idea that the IMHV serves as a storage site for visual imprinting. Imprinting alters the responses of neurons in the IMHV so that they become more likely to respond selectively to the imprinted stimulus. Some neurons are highly selective, whereas others generalize across colour or shape, or across distance or size. These neurons might mediate behavioural generalization and allow chicks to approach objects that resemble the imprinted stimulus. Early changes in synaptic transmission occur after imprinting. These include an increase in the size of the postsynaptic density of spine synapses and an increase in the number of NMDA ( N -methyl- D -aspartate) receptors in the left IMHV. Imprinting also causes a learning-related increase in the phosphorylation of the myristoylated alanine-rich protein kinase C (MARCKS) in the left IMHV, which is proposed to lead to an increase in vesicle availability in synapses. Some of these properties resemble those of hippocampal long-term potentiation. The left IMHV also probably undergoes changes in inhibitory signalling after imprinting. Both GABA (γ-aminobutyric acid) and taurine show a transient, learning-related increase in release. Increased inhibitory activity in the IMHV might shape the responses of neurons to specific visual stimuli. Later changes in synaptic transmission after imprinting include a learning-related increase in clathrin heavy-chain protein 24 h after training. This might predict that the turnover and/or number of synaptic vesicles in the IMHV increases after imprinting, as it does in the region after passive avoidance learning. The synaptic changes in the IMHV that are associated with imprinting also depend on behavioural state, which might be mediated by heterosynaptic inputs from other systems. The changes might be stabilized in the long term by an increase in levels of neural cell adhesion molecules, which is seen 24 h after training in the left IMHV. Studies that have tracked changes in neuronal responsiveness to imprinted or non-imprinted stimuli indicate that responsiveness to the imprinting stimulus waxes and wanes over the hours after training. During periods of lower responsiveness, a secondary store termed S′, elsewhere in the brain, is thought to mediate the behavioural preference for the imprinted stimulus. Cross-correlation analyses of neuronal activity in IMHV do not support the idea that connections between neurons that respond to the imprinting stimulus are selectively strengthened during imprinting (in a 'Hebbian assembly'). Rather, the neurons might form a set of parallel, largely uncoupled elements that are likely to provide a larger storage capacity than a system with tightly coupled elements. Memory is central to many aspects of behaviour, but in spite of a long interest in its neural basis, empirical evidence of the nature of the hypothetical pathway that is left in the vertebrate central nervous system by learning has been elusive. An important impediment has been the difficulty of localizing a brain region in which information is stored, but this difficulty has largely been overcome in the case of the learning process of visual imprinting. Most theories of memory suppose that an experience or event leads to the formation or strengthening of particular pathways in the brain. The evidence that is derived from imprinting partly supports this view, but the processes involved are more complex and more interesting than has been supposed.